Does conflict disrupt growth? Evidence of the relationship between political instability and national economic performance - Solomon W. Polachek; Daria Sevastianova (Institute for the Study of Labor (IZA), 2010)
Current empirical growth models limit the determinants of country growth to geographic, economic, and institutional variables. This study draws on conflict variables from the Correlates of War (COW) project to ask a critical question: How do different types of conflict affect country growth rates? It finds that wars slow the economy. Estimates indicate that civil war reduces annual growth by .01 to .13 percentage points, and high-intensity interstate conflict reduces annual growth by .18 to 2.77 percentage points. On the other hand, low-intensity conflict slows growth much less than high-intensity conflict, and may slightly increase it. The detrimental effect of conflict on growth is intensified when examining non-democracies, low income countries, and countries in Africa.
Keywords: C2; O1; O47; O57; P47; P52; 330; Economic growth; war; conflict; Politischer Konflikt; Politische Unruhen; Krieg; Bürgerkrieg; Wirtschaftswachstum; Schätzung; Welt